Increased Yield Surplus of Vetch-Wheat Rotations under Drought in a Mediterranean Environment. (2nd May 2012) - Dalias, Panagiotis
Abstract : This paper presents results of a plot-scale field experiment aiming at the comparative evaluation of agricultural practices and agricultural systems as far as their performance in very-low-rainfall conditions is concerned. Wheat was seeded after common vetch, treated in three different ways, after fallow or after the incorporation of dried sewage sludge or straw. Grain and straw yields and grain characteristics were always compared with conventional wheat monoculture without any additional organic inputs. Results showed a clear positive effect of vetch on next year's wheat yield and an increase in grain protein. Not only did the exceptionally dry season mask this effect, but also vetch-wheat systems were proved to be more effective in restraining wheat yield reductions, which are unavoidable under drought, marking these systems the most promising for improving sustainability and stability of rainfed agriculture.